Whole Exome Sequencing Identified a Novel Heterozygous Mutation in HMBS Gene in a Chinese Patient With Acute Intermittent Porphyria With Rare Type of Mild Anemia - Zheng, Yongjiang; Xu, Jiehua; Liang, Shengran; Lin, Dongjun; Banerjee, Santasree (Frontiers in Genetics, 2018)
Abstract Acute intermittent porphyria (AIP) is a rare hereditary metabolic disease with an autosomal dominant mode of inheritance. Germline mutations of HMBS gene causes AIP. Mutation of HMBS gene results into the partial deﬁciency of the heme biosynthetic enzyme hydroxymethylbilane synthase. AIP is clinically manifested with abdominal pain, vomiting, and neurological complaints. Additionally, an extreme phenotypic heterogeneity has been reported in AIP patients with mutations in HMBS gene. Here, we investigated a Chinese patient with AIP. The proband is a 28 years old Chinese male manifested with severe stomach ache, constipation, nausea and depression. Proband’s father and mother is normal. Proband’s blood sample was collected and genomic DNA was extracted. Whole exome sequencing and Sanger sequencing identified a heterozygous novel single nucleotide deletion (c.809delC) in exon 12 of HMBS gene in the proband. This mutation leads to frameshift followed by formation of a truncated (p.Ala270Valfs*2) HMBS protein with 272 amino acids comparing with the wild type HMBS protein of 361 amino acids. This mutation has not been found in proband’s unaffected parents as well as in 100 healthy normal control. According to the variant interpretation guidelines of American College of Medical Genetics and Genomics (ACMG), this variant is classified as “likely pathogenic” variant. Our findings expand the mutational spectra of HMBS gene related AIP which are significant for screening and genetic diagnosis for AIP.